2008
DOI: 10.1111/j.1532-849x.2008.00305.x
|View full text |Cite
|
Sign up to set email alerts
|

Fracture Strength and Fatigue Resistance of All‐Ceramic Molar Crowns Manufactured with CAD/CAM Technology

Abstract: The performance of VMII crowns was superior to YZ crowns in the fatigue test. The premature fractures and cracks of the YZ crowns were attributed to weakness in the YZ veneer layer or in the core/veneer bond.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
95
0
15

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(116 citation statements)
references
References 36 publications
(74 reference statements)
3
95
0
15
Order By: Relevance
“…The intermediate elastic modulus of zirconia is an advantage in reinforced layered structures, shifting damage and fracture modes into the porcelain veneer layer (Kim et al, 2007a). Only recently reported is a fatigue study on anatomically correct crowns which reported cohesive failure in the porcelain veneer and in the veneer/core bond (Zahran et al, 2008). This study used uni-axial loading, where the tooth-cusp-simulating indenter did not lift off the porcelain.…”
Section: Introduction Dmentioning
confidence: 99%
“…The intermediate elastic modulus of zirconia is an advantage in reinforced layered structures, shifting damage and fracture modes into the porcelain veneer layer (Kim et al, 2007a). Only recently reported is a fatigue study on anatomically correct crowns which reported cohesive failure in the porcelain veneer and in the veneer/core bond (Zahran et al, 2008). This study used uni-axial loading, where the tooth-cusp-simulating indenter did not lift off the porcelain.…”
Section: Introduction Dmentioning
confidence: 99%
“…The fracture load on the crowns with a dense zirconia frame was 1,930 N and on those with a commercial zirconia frame was 1,863 N. Larrson et al 23) reported that the fracture load of a crown with a dense zirconia frame made by milling a completely sintered zirconia block in the same manner as was done in our experiment was 1,800 N; and Ereifej et al 24) and Zahran et al 25) also stated in their reports that the fracture load of a crown with a dense zirconia frame designed for a lower molar was 2,081 N (Ereifej) and 1,459 N (Zahran) . However, one cannot compare these results one-for-one, because the experimental conditions including the abutment design, the shape and location of the crowns, the point of loading and the loading method varied from one experiment to another.…”
Section: Discussionmentioning
confidence: 52%
“…In previous reports [23][24][25] , there were fractures or dislodgements of the porcelain veneer from frames after fracture testing. By contrast, for five of the seven crowns with a hybrid zirconia frame, the zirconia frame fractured with the veneering porcelain still stuck to it, exposing the abutment tooth.…”
Section: Discussionmentioning
confidence: 99%
“…Bu yüzden çalıĢmamız in vitro ortamda gerçek-leĢtirilmiĢtir. 37 Tam seramik kuronlarda kırılma dayanı-mının değerlendirildiği çoğu çalıĢmada güdük materyali olarak metal 21,38,39 , pirinç 40,41 , epoksi rezin 21,38,42,43 ve dentin 21,44 kullanılmıĢtır. Bu çalıĢmada da bu amaçla klinik ortamı taklit edebilmek ve standardizasyonu sağlayabilmek için dentinin elastik modülüne yakın güdük materyali arayıĢına girilmiĢtir.…”
Section: Materyal Ve Metotunclassified